(untitled) (International relations and international law Journal, 2016)
In the context of international relations system fault information warfare, and in particular cyber network war, are of particular importance, comparable to the "traditional" war. Cyber and network operations are directed either to protect their information systems, or to attack the opposing party in order to make it difficult or even impossible to take them right decisions. Cyber wars do not have clear national and geographical boundaries. The objects of their impact are military and production (economic sphere) and civic networks, likewise political and public administration sphere. Cybernetic special units established in Germany and China have common and distinctive features. It is recognized that urgent task is to develop an international mechanism, norms and rules information exchange network exclusive manifestation of domination, invasion, cyber wars and conflicts.